Income and Wealth Inequalities in Thomas Piketty’s Considerations - Danowska-Prokop Barbara (Studies in Logic, Grammar and Rhetoric, 2023)
(Purpose) The purpose of the study is to present Thomas Piketty’s demand view on the issue of growing income and wealth inequalities in highly industrialized countries. It should be indicated here that in his research, Piketty not only explains the mechanism of growing inequalities, but also defines the tools to tackle inequalities (a combination of theoretical and pragmatic views). (Methodology) The aim of the study is achieved through the literature review method as well as the descriptive methods, complemented by comparative analysis.